Eficácia antibacteriana in vivo da solução otológica à base de spondias mombin l. no tratamento de otite externa em cães - Silva, Jonas dos Santos (Universidade Federal Rural do Semi-Árido, 2021)
Studies show that Spondias mombin L. (SM) has bioactives with antimicrobial potential, which can be used alternatively in veterinary medicine, being an option in cases of canine infections with multiresistant bacteria. Thus, the aim of this study was to evaluate the in vivo antibacterial efficacy of the otological solution based on SM leaves in the treatment of otitis externa in dogs. Twenty animals were used, regardless of sex, race and age, which presented a series of otitis, which were divided into four groups of 5 animals, submitted to the action of the test solution based on SM (2% - glycerin and applied 12/ 12h; 2% - glycerin and applied 24/24h; 20% applied 12/12h) and positive control ciprofloxacin 3.5%, evaluated at 7, 14 and 21 days after the start of treatment. In each group, ear secretion was collected with the aid of swabs and the bacterial quantity was evaluated according to the serial dilution technique (10¹ to 104), seeded in Plate Count agar, in duplicate. The microorganisms isolated at the beginning of the treatments were submitted to morphotintorial analysis and biochemical tests to conclude their genus/species and identification of their resistance to antibiotics (antibiogram). Clinical signs (itching, pain, hyperpigmentation, hyperkeratosis, erythema, desquamation and exudate) of the auditory meatus were assessed using a checklist (0, 7, 14 and 21 days) attributing scores ranging from 0 (absence of symptoms) to +5 (critical level of symptomatology) for macroscopic determination of treatment efficacy. The evaluation of the plant's cytotoxicity was carried out using a canine skin fragment (9.0mm3), divided into four groups and incubated for 12h for each group: a) Without the presence of extract; b) 20% caja extract; c) 2% caja extract; d) 3.5% ciprofloxacin solution, analyzing cell morphology, viability and metabolic activity. Descriptive statistics were associated with the number and percentage of species and bacterial resistance. As for the quantification of bacteria, cytotoxicity and clinical signs, they were submitted to analysis of variance (ANOVA) and when significance was found between treatments, the mean comparison test (Tukey 5%) was applied with the statistical program SISVAR 5.6. For cytotoxicity, data were expressed as mean ± standard error of four replications, using the GraphPad software (Graph-Pad Software Incorporation, La Jolla, CA, USA), the results were checked for normality by the Shapiro-Wilk test and homoscedasticity by the Levene's test. In the in vitro test (antibiogram), of the 33 bacterial strains isolated, 32 showed resistance to at least one antimicrobial and 9 were resistant to three or more different antimicrobials. As for clinical signs, the scores for itching, pain, hyperpigmentation, desquamation, erythema and exudate in the treatment with MS (2% - glycerin and 20% applied at 12/12h) were similar to the positive control (p<0, 05). Concluding that the 2% SM otologic solution with glycerin (12/12h) has a tendency as an alternative herbal medicine to decrease bacterial counts and clinical signs in dog otitis
Keywords: Plantas medicinais; Antimicrobiano; Otite canina; Contagem bacteriana; Citotoxicidade; Medicinal plants; Antimicrobial; Canine otitis; Bacterial count; Cytotoxicity; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE